"The Legal Framework for Cybersecurity in Iraq: An Analytical Study Based on National Laws and International Standards - Sabbar Razzaq Sajit Al-Hamdan, Researcher. Sajjad; Heydari , Assist. Prof. Elham (Basra studies journal, 2025)
With the rapid advancement of information technology, cybersecurity has become essential for protecting digital infrastructure and ensuring national security. Iraq faces growing challenges in securing its cyberspace, necessitating a comprehensive legal framework to combat cybercrime. This study aims to analyze Iraqi cybersecurity legislation, assess its alignment with international standards, and identify gaps while proposing measures to address them. The findings indicate that the current legal framework is insufficient to keep pace with evolving cyber threats, lacking clear regulations and effective mechanisms for mitigating such threats. The study recommends updating cybersecurity laws, adopting international best practices, and enhancing cooperation among relevant entities to ensure a more effective response to cyber threats.